Glial cells and neurologic autoimmune disorders - Li, Zhao-Qing; Li, Tong-Xin; Tian, Miao; Ren, Ze-Sheng; Yuan, Chen-Yi; Yang, Rui-Kun; Shi, Su-Juan; Li, Hui; Kou, Zhen-Zhen (Frontiers in Cellular Neuroscience, 2022)
Neurologic autoimmune disorders affect people’s physical and mental health seriously. Glial cells, as an important part of the nervous system, play a vital role in the occurrence of neurologic autoimmune disorders. Glial cells can be hyperactivated in the presence of autoantibodies or pathological changes, to influence neurologic autoimmune disorders. This review is mainly focused on the roles of glial cells in neurologic autoimmune disorders and the influence of autoantibodies produced by autoimmune disorders on glial cells. We speculate that the possibility of glial cells might be a novel way for the investigation and therapy of neurologic autoimmune disorders.